A novel technique for performing transseptal puncture guided by a non‐fluoroscopic 3D mapping system. Issue 1 (28th November 2018) - Sawhney, Vinit; Breitenstein, Alexander; Watts, Troy; Garcia, Jason; Finlay, Malcolm; Lowe, Martin; Hunter, Ross; Earley, Mark J; Schilling, Richard J; Sporton, Simon; Dhinoja, Mehul
Abstract: Background: Transseptal puncture (TSP) is commonly performed under fluoroscopic guidance in left atrial ablation procedures. This exposes patients and healthcare professionals to deleterious ionizing radiation. We describe a novel technique for performing TSP non‐fluoroscopically using a three‐dimensional (3D) mapping system only. The safety and efficacy of this technique is compared to traditional fluoroscopy guided TSP. Methods: Retrospective, single‐center study of patients undergoing TSP for left atrial ablation. Those undergoing TSP using 3D mapping system alone (nonfluoroscopy group) were compared to those undergoing fluoroscopic guided TSP (Fluoroscopy group). Clinical, procedural data and complications were analyzed from a prospective registry. Results: Twenty patients (32 TSPs) in the nonfluoroscopy (NF) group were compared to 14 patients (25 TSPs) in fluoroscopy (F) group. TSP success rates were similar across the groups (88% vs 96% in the NF and F groups, P  = 0.97). In the NF group, there was one cardiac tamponade, two unsuccessful TSPs (previous cardiac surgery—required TOE guided TSP), and one patient required fluoroscopy on a background of CRTD device to avoid lead displacement. The mean fluoroscopy time and dose were significantly lower in the nonfluoroscopy group (0.75  ±  0.50 vs 5.32 ± 3.23 min, P   <  0.001; 92.5 ± 60.7 vs 394.3 ± 182.7 cGy/cm 2, P  < 0.001). Conclusion: Our study shows that TSPs can be performed safely and effectively using this non‐fluoroscopic novel technique in a select group of patients. Radiation exposure is reduced significantly without compromising patient safety. Larger studies are required to substantiate these results. Patients with cardiac implantable devices and previous cardiac surgery may pose a challenge to using this technique.